LE « LIEMBA » CHEZ LES TOPOKE : UNE ORGANISATION D’AUTO DEVELOPPEMENT RURAL DU SECTEUR LOKOMBE EN TERRITOIRE D’ISANGI (RD CONGO). - ASAKA John, ANGONDO; BESINGELA BOLOMBI Esaïe,; IDJUMBE WOLA Prosper, (IJRDO - Journal of Social Science and Humanities Research, 2019)
The young people of LOKOMBE sector met around a structure named « LIEMBA » which is a regroupment of young people but for distinction of categories are determined of selves taking in load by taking into account of theirs needs. It’s concerned to realize certain susceptible activities to resolve the principle preoccupations which hobble the development of their vital arced.